Penerapan Flex Coil Pada Pemeriksaan Mri Wrist Joint Dengan Klinis Fraktur Inkomplit Styloid Ulna - Afrida, Celly; Mahendra, I made Adhi; Arianjani, Dini (Innovative: Journal Of Social Science Research, 2025)
MRI (Magnetic Resonance Imaging) examination is a superior diagnostic imaging method that is able to provide accurate soft tissue details, including in the wrist joint area. In practice, the use of flex Coil is an important alternative when a special Coil is not available, such as in the case of a Hospital in Bekasi. This report aims to evaluate the role of flex Coil in MRI examination of the wrist joint with clinical incomplete fracture of the ulna styloid. This study uses a descriptive approach through observation, interviews, and documentation in a 19-year-old female patient. The examination was carried out using MRI 1.5 TESLA and flex Coil as a substitute for the wrist Coil. The imaging results showed an incomplete fracture of the ulna styloid without other soft tissue damage. Flex Coil has been proven to provide adequate image quality for diagnostic purposes, as well as being an efficient and adaptive solution to limited facilities. Thus, the flexibility of the tool and operator competence are important factors in optimizing MRI examination results. Keywords: Flex Coil, MRI, Wrist Joint, Incomplete Fracture, Styloid Ulna